2019
DOI: 10.1186/s12940-019-0517-z
|View full text |Cite
|
Sign up to set email alerts
|

Personal carbon monoxide exposure, respiratory symptoms, and the potentially modifying roles of sex and HIV infection in rural Uganda: a cohort study

Abstract: Background Most of the global burden of pollution-related morbidity and mortality is believed to occur in resource-limited settings, where HIV serostatus and sex may influence the relationship between air pollution exposure and respiratory morbidity. The lack of air quality monitoring networks in these settings limits progress in measuring global disparities in pollution-related health. Personal carbon monoxide monitoring may identify sub-populations at heightened risk for air pollution-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 63 publications
1
21
0
1
Order By: Relevance
“…Increased CO concentrations in the air were accompanied by increased R 0 . Previous studies have indicated that CO exposure is associated with respiratory symptoms ( Zhao et al, 2019 ; North et al, 2019 ; Lawin et al, 2018 ). Therefore, COVID-19 as a respiratory disease may be associated with high level CO exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Increased CO concentrations in the air were accompanied by increased R 0 . Previous studies have indicated that CO exposure is associated with respiratory symptoms ( Zhao et al, 2019 ; North et al, 2019 ; Lawin et al, 2018 ). Therefore, COVID-19 as a respiratory disease may be associated with high level CO exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences among PLHIV may differ by geographic location, race and cultural practices. For example, in Uganda, females with and without HIV are exposed to more carbon monoxide via indoor cook stoves compared to males [ 22 ], which is known to be associated with increased CVD mortality [ 23 ]. This may partly explain why inflammation markers are higher in Ugandan females compared to males [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Continuous exposure to CO will cause respiratory problems. A previous study showed a correlation between CO pollution and respiratory diseases (21). The average annual prevalence of respiratory diseases in the experimental group who breathed air pollution was 57.17%.…”
Section: Discussionmentioning
confidence: 68%